Surface Modification of Dental Titanium Implant by Layer-by-Layer Electrostatic Self-Assembly - Shi, Quan; Qian, Zhiyong; Liu, Donghua; Liu, Hongchen (Frontiers in Physiology, 2017)
In vivo implants that are composed of titanium and titanium alloys as raw materials are widely used in the fields of biology and medicine. In the field of dental medicine, titanium is considered to be an ideal dental implant material. Good osseointegration and soft tissue closure are the foundation for the success of dental implants. Therefore, the enhancement of the osseointegration and antibacterial abilities of titanium and its alloys has been the focus of much research. With its many advantages, layer-by-layer (LbL) assembly is a self-assembly technique that is used to develop multilayer films based on complementary interactions between differently charged polyelectrolytes. The LbL approach provides new methods and applications for the surface modification of dental titanium implant. In this review, the application of the LbL technique to surface modification of titanium including promoting osteogenesis and osseointegration, promoting the formation and healing of soft tissues, improving the antibacterial properties of titanium implant, achieving local drug delivery and sustained release is summarized.